Taper Tantrum and Emerging Equity Market Slumps - Gemma B. Estrada; Donghyun Park; Arief Ramayandi (Asian Development Bank (ADB), 2015)
In the postglobal financial crisis period, the central banks of the advanced economies pursued unconventional monetary policies, such as the United States (US) Federal Reserve's quantitative easing (QE). Those policies and their unwinding may significantly affect cross-border capital flows and thus destabilize the financial systems of emerging markets. For example, emerging markets experienced substantial financial instability during the taper tantrum triggered by the US Federal Reserve Chairman Ben Bernanke's May 2013 announcement of the potential unwinding of QE. In this paper, we examine the spillovers from the taper tantrum on emerging markets more rigorously by using econometric analysis to empirically assess the effect on equity markets in emerging markets. Our central finding that virtually all emerging market equity markets were affected by the taper tantrum highlights the need for emerging market authorities to remain vigilant about the effects of advanced economy monetary policies on their financial stability.
hdl:11540/5156
Keywords: F32; G15; 330; capital flows; emerging market; equity market; financial stability; global financial crisis; quantitative easing; taper tantrum